(y+3)-(y-5)=7

Simple and best practice solution for (y+3)-(y-5)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+3)-(y-5)=7 equation:


Simplifying
(y + 3) + -1(y + -5) = 7

Reorder the terms:
(3 + y) + -1(y + -5) = 7

Remove parenthesis around (3 + y)
3 + y + -1(y + -5) = 7

Reorder the terms:
3 + y + -1(-5 + y) = 7
3 + y + (-5 * -1 + y * -1) = 7
3 + y + (5 + -1y) = 7

Reorder the terms:
3 + 5 + y + -1y = 7

Combine like terms: 3 + 5 = 8
8 + y + -1y = 7

Combine like terms: y + -1y = 0
8 + 0 = 7
8 = 7

Solving
8 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10-7x=6x+101 | | 5(y-3)+(2y-9)=8 | | y+2-2=15-2 | | f(-3)=-5 | | -6=n/2/10 | | 5-r/1.3=7.4 | | -120=-5(6-3v) | | 12q^2=4 | | 2(2x+9)-2=3(3x-8) | | t^2-70+8=0 | | 2(2x+9)-2=3(3x+8) | | 5-(5+3x)=x-20 | | 4x+4/6=3x-4 | | 5a(7a+7)=1 | | 7m+24=9 | | 3p+5q=-4 | | 20/x=x+1 | | 5-n=2 | | 5x+7=63-x | | 3q+5q=-4 | | 9x-7y=19fory | | -4a+8=16 | | 4(x+1)/6 | | x-8y=13fory | | 8+3q-3q=8 | | 53=-4x+9 | | 4x^2-136=264 | | 3q-p=8 | | 144/55*11/12 | | p-3q=8 | | x^2+30x+110=0 | | -3n-8=49 |

Equations solver categories